Monitoring of a watershed environment using remote sensing and GIS - Mohd Soom, Mohd Amin; Nabi, Amjad; Khatun, Abeda (Universiti Putra Malaysia, 1999)
Deforestation and land development for agriculture and urbanisation are affecting the watershed environment especially its water resources. Remote sensing data and GIS can be used to estimate some parameters and simulate the effects of vegetation and climate on water yield of a vegetated watershed. A distributed modelling approach was used to estimate the water transfers of different hydrologic phases and the discharge at the outlet of a 66 km2 watershed in the state of Perak, Malaysia. Landsat TM data was used to subdivide the watershed into hydrologically homogeneous ground response units in a GIS environment. Leaf area index (LAI) as an important structural variable to quantify energy and mass exchange was estimated from the TM data. A comparison of modelled water yield obtained from the satellite data and GIS estimates showed a good match from both annual and monthly water yields. Hence remote sensing and GIS are useful in environmental management as it reasonably estimate the vegetation and climatic changes, and good tools to initialize a regional water balance. Managers of irrigation schemes which usually use about 80% of the total fresh available water will benefit from incorporation of remote sensing data in a GIS environment as a part of their management tools.